ANALISIS FAKTOR DETERMINAN TAX AVOIDANCE (STUDI EMPIRIS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2020) - Fitrianingrum, Erika; Setiawati, Erma (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
The high number of cases of tax avoidance in Indonesia, encourages to conduct research on factors that affect tax avoidance. Tax avoidance is an action taken by taxpayers to minimize tax payments. Differences in interests between taxpayers and the government in responding to taxes, of course, will lead to tax avoidance actions carried out by taxpayers by exploiting loopholes in the Tax Law. This study aims to determine the influence of independent commissioners on tax avoidance, the influence of leverage on tax avoidance, the influence of profitability on tax avoidance, the influence of sales growth on tax avoidance, and the influence of company size on tax avoidance. The method used in this study is the quantitative method. The study used secondary data obtained from the annual reports of manufacturing companies listed on the Indonesia Stock Exchange during 2018 to 2020 downloaded through www.idx.co.id. The population used in the study was 492 companies, samples taken in the study as many as 231 companies, which were selected using purposive sampling techniques. The data analysis technique used in this study is multiple regression analysis for sample data. The results of this study concluded that independent commissioners have no effect on tax avoidance, leverage has no effect on tax avoidance, sales growth has no effect on tax avoidance, and company size has no effect on tax avoidance. While profitability affects tax avoidance.